Gambling and violence in a nationally representative sample of UK men - Amanda Roberts; Jeremy Coid; Robert King; Raegan Murphy; John Turner; Henrietta Bowden‐Jones; Katie Palmer du Preez; Jason Landon (2016)
Abstract Background and Aims The relationship between violence and problem gambling in general population samples is under‐researched and requires further attention to inform treatment and prevention efforts. We investigated the relationship between gambling problems and violence among men and sought to determine if the link can be accounted for by mental disorders, alcohol and drug dependence and impulsivity. Design A cross‐sectional survey. Setting A UK representative general population survey conducted in 2009. Participants A total of 3025 UK men aged 18–64 years. Measurements Binary logistic regression was used to examine relationships. Outcome measures included gambling behaviour and self‐reports of violence. Covariates included alcohol and drug dependence, mental illness, impulsivity and socio‐demography. Findings Problem gambling and probable pathological gambling were associated with increased odds of the perpetration of violence [adjusted odd ratios (AOR) = 3.09, confidence interval (CI) = 1.90–5.00 and 4.09, CI = 2.76–6.30, respectively] and a range of other behaviours, such as using a weapon (AORs = 4.93, CI = 2.52–9.63 and 6.33, CI = 3.52–11.38) and the perpetration of intimate partner violence (AOR = 9.80, CI =2.45–39.04). The results were attenuated when adjusted for comorbid mental illness and impulsivity, but remained statistically significant. Alcohol and drug dependence had the most impact; relationships were most attenuated when they added into the models, with the latter having the largest effect. Conclusions Among men in the United Kingdom, self‐reports of problem/pathological gambling remain predictive of a range of measures of violent behaviour after adjusting for alcohol and drug dependence, comorbid mental disorder and impulsivity; of the covariates, alcohol and drug dependence have the greatest effect in attenuating the gambling‐violence association.